Perancangan Sistem Informasi Distribusi Barang Menggunakan BlueSeer Enterprise Resource Planning - Heri Purwanto; Taupik Ridwan; Yanwar Aryanggara (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
One of the current operational activities of PT. Geoff Maksimal Jaya is the distribution of goods, every item that has been produced will be stored in the warehouse to be entrusted or distributed to shops, wholesalers, and other related parties. However, data documentation activities related to the distribution of these goods are still carried out manually, so that access to obtain any information is still limited. In response to these problems, the purpose of this study was made to get easy access to information by utilizing the BlueSeer ERP application as a reference for designing information systems. The development method used in this research is the waterfall. It is hoped that this can help companies access information on operational activities of distributing goods effectively and efficiently. In the future, this research can be developed by adding several other aspects such as monitoring the delivery of goods in order to cover the complete access to information on operational activities of the distribution of goods.